182k views
17 votes
Y=3x
Y=x+4
What is substitute and the solution?

User Tim Wilcox
by
6.0k points

1 Answer

9 votes

take the second equation and plug it into the first one after you set it equal to x.

so y+4=x then plug it into the first equation.

y=y+4-4

then 4-4=0

so your answer would be y=y which would make it be no solution

3x = x - 4

x = -2

Since y = 3x, then y = 3(-2) = -6. It also satisfies the second equation

how do you solve

y=3x

y=x-4

using substitution

----------

3x = x-4

2x = -4

x = -2

--------

y = -6

User Gusdor
by
6.9k points